2020
DOI: 10.1016/j.xphs.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-Induced Surface Freezing for the Freeze-Drying of the Human Growth Hormone: How Does Nucleation Control Affect Protein Stability?

Abstract: In the present work, the effect of controlled nucleation on the stability of human growth hormone (hGH) during freeze-drying has been investigated. More specifically, the vacuum-induced surface freezing technique has been compared to conventional freezing, both with and without an annealing step. Size exclusion chromatography and cell-based potency assays have been used to characterize the formation of soluble aggregates and the biological activity of hGH, respectively. The results obtained indicate that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 52 publications
1
12
0
Order By: Relevance
“…The freezing step has been recently studied in detail as it was proven to substantially influence the product structure [ 4 , 5 , 6 ] and the drug residual activity [ 7 , 8 , 9 , 10 ]. When water is cooled below its equilibrium temperature, it can remain in the liquid state for a relatively long time before the occurrence of the phase transition into solid ice.…”
Section: Introductionmentioning
confidence: 99%
“…The freezing step has been recently studied in detail as it was proven to substantially influence the product structure [ 4 , 5 , 6 ] and the drug residual activity [ 7 , 8 , 9 , 10 ]. When water is cooled below its equilibrium temperature, it can remain in the liquid state for a relatively long time before the occurrence of the phase transition into solid ice.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even though economic evaluations have been presented in the past [9][10][11], they are often too broad or too specific to be used for making comparisons between different process strategies. Whereas little effort has been made in this field to determine the economic impact of freeze-drying quantitatively, the optimization of the process has usually remained product-or quality-specific [12][13][14][15][16][17][18], with no considerations of possible bottlenecks in the expenses. In this work, we aim to create a model to evaluate the actual economic impact of a freeze-drying cycle, and evaluate the impact of process parameters on processing costs and, finally, the benefits of process optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Although solid-state properties differed slightly, they concluded that controlled ice nucleation had neither a positive nor negative impact on protein stability compared to stochastically nucleated samples. Oddone et al reported no difference in stability of stochastic versus controlled nucleation vials by the "partial vacuum" method investigated for different formulations of human growth hormone [22]. The current study focused on investigating and comparing the impact of three mechanistically different nucleation techniques on protein stability and included challenging protein configurations.…”
Section: Comparability Of Product Attributesmentioning
confidence: 96%